Linguistic and Visual Patterns of ChatGPT in Higher Education: An Analysis of its Use in Undergraduate Theses - Peña Cáceres, Oscar; Sánchez-Rogel, Elvis; Barros-Naranjo, Jhon; Silva-Marchan, Henry; Espinoza-Nima, Rudy; Correa-Calle, Teofilo (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
This article examines the influence of artificial intelligence in academic writing, focusing on undergraduate theses. Its objective is to identify linguistic and visual patterns in texts generated or assisted by ChatGPT, through an analysis of 50 undergraduate and master's theses, equally distributed between a public and a private university in Peru. The results indicate that the most representative argumentative structures include terms such as “in addition”, “crucial role” and “exhaustive”. A 48% argumentative similarity was observed in the public university, in contrast to 72% in the private university. It is recommended to extend the analysis with other language models, such as BART.